Efeito do exercício físico sobre o desenvolvimento de crises convulsivas pós-traumáticas em ratos: o papel da trombina - Nascimento, Alexandre Seixas (2023)
Traumatic brain injury (TBI) affects about 69 million people worldwide and is the major cause of post-traumatic epilepsy (PTE), a structural acquired type of epilepsy where acute seizures onset can influence the pathophysiology progress of this disease. The blood-brain barrier disruption after TBI promotes the extravasation of thrombin, a serine protease from clotting pathway to brain parenchyma, which can promote PAR1 hyperactivation, leading to neuronal excitability, pro-inflammatory cytokines production and aberrant cell proliferation in central nervous system, facilitating seizure onset. In this meaning, the present study aimed to evaluate the effect of a previous long-term physical exercise protocol in acute post-traumatic seizure onset thought thrombin modulation in an experimental model. For that, male Wistar rats were divided in experiment 1, where Naïve and Sham animals were compared to animals submitted to a severe TBI thought lateral fluid percussion injury (3.0 atm), monitored though electroencephalogram (EEG) recording and 6h following trauma were euthanized to neurochemical analysis, and experiment 2, where animals went through a swimming training protocol and were injected (i.p.) with a PAR1 antagonist before TBI and then were EEG monitored and euthanized 6h following TBI to neurochemical analyses. Data from experiment 1 showed increase in epileptiform activity after TBI, as well as increased thrombin, PAR1, albumin, PKC, P70S6K, GFAP, TNF-α and IL-1β immunocontent in hippocampal samples. Also, TBI promoted decrease of GAD67 immunocontent as well as increase in CaMKII expression and Na+, N+-ATPase α1 activity, suggesting increase in BBB permeability, activation of cell proliferation mechanism, pro-inflammatory state, and neuronal gradient impairment. In addition, preventive physical exercise as well as PAR1 antagonism were capable of prevent the increased epileptic EEG parameters post-TBI, likely to thrombin/PAR1 upregulation, BBB breakdown, PKC/P70S6K activation, pro-inflammatory (TNF-α and IL-1β) cytokines production, modulation of CaMKII-mediated Na+, N+-ATPase α1 activity as well as GAD67 decrease. This data elucidates the mechanisms of chronic physical exercise prophylactic effects in post-traumatic seizure onset, although caveats about thrombin/PAR1 influence on seizure incidence must be considered, demanding more studies of this scope.